2009
DOI: 10.1128/jcm.01161-08
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin-Resistant Salmonella enterica Serovar Typhi from Kuwait with Novel Mutations in gyrA and parC Genes

Abstract: Blood isolates of Salmonella enterica serovar Typhi from two recently returned Bangladeshi patients in Kuwait were ciprofloxacin resistant, with ciprofloxacin MICs of 12 mg/liter for both isolates. Both isolates had three novel gyrA mutations (55-Leu3Trp, 87-Asp3Ala, and 106-Gln3Arg) and three novel parC mutations (84-Glu3Lys, 106-Trp3Gly, and 128-Tyr3Asp).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 26 publications
(27 reference statements)
3
38
0
2
Order By: Relevance
“…in Cambodia, where S. typhi susceptibility to ciprofloxacin and ceftriaxone were 79% and 81% respectively. Similarly, a study on ciprofloxacin resistant S. typhi and treatment failure in the Kuwait by Dimitrov et al 18 also revealed susceptibility of 63.3% and 67.3% for ciprofloxacin and ceftriaxone respectively, which were considered to be high. The high susceptibility of S. typhi to ciprofloxacin and ceftriaxone recorded at the three hospitals may be due to the fact that ciprofloxacin and ceftriaxone have recently been introduced on the Ghanaian market and so might not have been subjected to abuse as compared to ampicillin 9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in Cambodia, where S. typhi susceptibility to ciprofloxacin and ceftriaxone were 79% and 81% respectively. Similarly, a study on ciprofloxacin resistant S. typhi and treatment failure in the Kuwait by Dimitrov et al 18 also revealed susceptibility of 63.3% and 67.3% for ciprofloxacin and ceftriaxone respectively, which were considered to be high. The high susceptibility of S. typhi to ciprofloxacin and ceftriaxone recorded at the three hospitals may be due to the fact that ciprofloxacin and ceftriaxone have recently been introduced on the Ghanaian market and so might not have been subjected to abuse as compared to ampicillin 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Some other factors identified in literature as the drivers of bacterial resistance to antibiotics such as unnecessary prescriptions and substandard antibiotics could also be the cause of the S. typhi resistance observed against the antibiotics in this study 17,18 . The usefulness of these antibiotics will therefore depend on the effective interventions put in place by health authorities to curb the spread of resistance among bacterial strains to antibiotics 7 .…”
Section: Figure 2: Antimicrobial Susceptibility Patterns Of S Typhi mentioning
confidence: 99%
“…Ainsi, des souches hautement résistantes à la ciprofloxacine (CMI ≥ 4 mg/l) originaires du sous-continent indien ont été identifiées ; elles restent toutefois rares puisqu'elles ne représentaient que 0,2 % (5 sur 2016) des souches isolées aux États-Unis entre 1999 et 2006 [25,26,32,33]. Une seule souche de ce type a été identifiée en France depuis 1997.…”
Section: La Résistance Aux Antibiotiques De Demainunclassified
“…Une seule souche de ce type a été identifiée en France depuis 1997. Ces souches dérivent des souches Nal R -Cip SD par acquisition de mutations chromosomiques additionnelles (une deuxième mutation dans le gène gyrA et une mutation dans le gène parC codant pour une sous-unité de la topoisomérase IV, cible secondaire des quinolones) [32] ou bien par acquisition d'un gène plasmidique de résistance aux quinolones appelé qnr [33]. En dehors du problème thérapeutique qu'elles posent (aucune fluoroquinolone ne peut être active), ces souches ne présentent pas de difficulté d'identification au niveau du laboratoire contrairement aux souches Cip SD .…”
Section: La Résistance Aux Antibiotiques De Demainunclassified
“…Mutation at the conserved Ser84 in parC was documented in many bacterial species to cause quinolone resistance (4,8). Moon et al reported that a mutation at codon 84 in parC, combined with mutations in gyrA at codons 83 and 87, led to high levels of resistance to fluoroquinolones in 10 E. coli isolates (8).…”
mentioning
confidence: 99%